Penerapan E-Court di Pengadilan Agama Pasuruan - Rizky Zahratul Wardah; Alief Tiyan Cahyani; Anindya Octaviani; Halimatus Syakdiyah; Helga Fatma Mandy Pramana; Intan Laili Eka Ramadhanti (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2020)
Abstract: In article 2 PERMA RI No. 3 of 2018 concerning Case Administration, states that as an electronic court, it is carried out to support the realization of an orderly case administration that is professional, transparent, accountable, effective, efficient, and modern. E-court is a service for Registered Users for e-Filing (Online Case Registration in Courts), e-Payment (Online Court Fee Payment), and e-Summons (Online Party Summons). There are several deficiencies that affect the E-Court system at the Pasuruan Religious Court, including: Lack of human resources who manage E-Court at the Pasuruan Religious Court, lack of knowledge of the litigants about the e-Court system, there are still many people in Pasuruan City who are lacking understand about the continuous development of IT with the E-Court system, at least people use the services of an advocate in the city of Pasuruan, because E-Court can only be used by parties who use the services of lawyers registered with the Supreme Court, and internet access has not been widespread in several the jurisdiction of the Pasuruan Religious Court, especially in remote cities. Keywords: Religious Courts, E-Court, effectiveness. Abstrak: Pada pasal 2 PERMA RI No. 3 Tahun 2018 tentang Administrasi Perkara, disebutkan bahwa sebagai pengadilan secara elektronik dilakukan untuk mendukung terwujudnya tertib administrasi perkara yang  profesional, transparan, akuntabel, efektif, efisien, dan modern. E-court adalah layanan bagi Pengguna Terdaftar untuk e-Filing (Pendaftaran Perkara Online di Pengadilan), e-Payment (Pembayaran Panjar Biaya Perkara Online), dan e-Summons (Pemanggilan Pihak secara online). Terdapat beberapa kekurangan yang mempengaruhi sistem E-Court di Pengadilan Agama Pasuruan, di antaranya: Kurangnya sumber daya manusia yang mengelola E-Court di Pengadilan Agama Pasuruan, kurangnya pengetahuan dari pihak yang berperkara tentang sistem e-Court, masih banyaknya masyarakat kota Pasuruan yang kurang mengerti tentang perkembangan IT yang berkesinambungan dengan sistem E-Court, sedikitnya masyarakat yang mengguanakan jasa dari seorang advokat di kota Pasuruan, karena E-Court hanya dapat digunakan pada pihak yang menggunakan jasa pengacara yang terdaftar di Mahkamah Agung, dan belum meluasnya akses internet di beberapa wilayah yuridiksi Pengadilan Agama Pasuruan, terutama di pelosok kota. Kata Kunci: Peradilan Agama, E-Court, efektifitas.